Gamification in Mathematics Teaching: from Paraná's Curricular Guidelines to classroom, via Teaching Work Plan (Research, Society and Development, 2019)
The objective of the present article is to present the partial results of a work that integrates the line of research “Teaching of Languages and its Technologies” (PPGENS/UNOPAR) and aims to elaborate and apply, in the classroom, a Teaching Work Plan, suggested by the Curricular Guidelines of the State of Paraná, having as programmatic content the theory of plane geometry, in Mathematics classes. The research is justified by the difficulties of the students of the 6th and 7th years of elementary school, related to this programmatic content. Thus, through a qualitative research, applied through action research, we adopt gamification as a tool, in favor of the teaching and learning process, aiming at linking theory and practice. The epistemological construct deals with the theory of the gamification and teaching. After the application of a Teaching Work Plan, the result indicated the proficiency of the classroom games, with a significant increase in students’ interest and motivation concerning their studies, as well as an appropriation of area concepts that are essential for the student’s education.